جودة الحياة و علاقتها بالضغوط المهنية لدى عمال قطاع الصحة دراسة ميدانية في مستشفى العقيد لطفي 240 سرير الاغواط - بومدين مريم; بلخير منصورة; هواري بوشهير (My University, 2023)
This study aimed to identify the nature of the relationship between quality of life and occupational stress in a sample of hospital workers for public health ، And measuring the level of both the quality of life and occupational pressures they have ،And study the differences in both variables between the sexes In this study ، were lied on the descriptive-correlation a approach ،and the research community was represented by employees from different groups working at the Public Health Institution Ben Aljia in the state of Laghouat We selected a random sample of 30workers of both sexes ،The tool of the study was the quality of life scale and the occupational stress scale ،where we did the statistical treatment through a set of tests such as the correlation coefficient and the significance of differences test. The results were as follows: There is a statistically significant relationship between quality of life and occupational stress among hospital staff in the state of Laghouat ،in addition to the existence of an average level for both ،and there are no statistically significant differences in both variables due to the gender variable. Keywords: quality of life ،occupational stress